A retrospective study of emergency obstetric hysterectomy in a tertiary care center for a period of 5 years - Sharma, Bhawna; Saxena, Namrata; Gupta, Vineeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The study was conducted to determine the frequency, demographic characteristics, indication and fetomaternal outcome associated with emergency obstetric hysterectomy in a tertiary care center. Methods: Thirty cases of emergency obstetric hysterectomy performed during the five-year period from April 2011 to April 2016 were analyzed in the dept. of Gynae and obs. in Shri Guru Ram Rai Institute of Medical Sciences in Dehradun. Results: During the study period there were 30 cases of obstetric hysterectomy out of 8084 deliveries giving an incidence of 0.37%. Majority of the patients (60%) were unbooked and were in the age group of 26-30 (43.3%). Common parity group were 3, 4 and 5. Morbid adherent placenta was the most common indication contributing to 40% of the cases. There were four maternal deaths in the study. All were unbooked and three of them died of hypovolemic shock with cardiopulmonary arrest and one died of septicemia. Whereas there were 60% perinatal mortality and 26.66% NICU admissions. Conclusions: Emergency obstetric hysterectomy is a potentially lifesaving procedure which often puts obstetrician in dilemma at the time of decision making.